Astenopia y disminución de agudeza visual de lejos en paciente de 28 años. - Garcés Vera, Keyla Jemina (2022)
This research work reflects more specifically what can cause visual stress (asthenopia) in a 28-year-old female patient, who comes to the clinic after finishing her workday with the following symptoms: headache (headache), burning, redness and decreased distance vision. This patient is the Administrator of an online business, and she had been noticing for several months that when she left the premises, she had these symptoms until she decided to go to the clinic. Once the anamnesis was completed, an optometric evaluation was carried out, where a decrease in distance visual acuity was found. When performing the refraction, it was possible to compensate for the ametropia, and through the use of optical aids, the adequate treatment of the refractive problem that he presented was carried out: right eye - myopia, left eye - astigmatism.